1992
DOI: 10.1111/j.1365-2125.1992.tb05644.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin converting enzyme inhibitors on erythropoietin concentrations in healthy volunteers.

Abstract: The possibility that the ACE inhibitors, enalapril and captopril, may decrease plasma EPO concentrations was studied in a single‐blind, cross‐ over study in 10 healthy volunteers. Plasma EPO concentrations, haemoglobin concentration, red blood cell count, plasma creatinine concentration and mean arterial pressure were measured at baseline and after 28 days treatment with both ACE inhibitors. A significant fall in mean plasma EPO concentration occurred with both ACE inhibitors and returned to baseline after sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 8 publications
1
54
0
2
Order By: Relevance
“…In some patients, ACE inhibitors may cause a small decrease in serum EPO levels with a nonsignificant reduction in Hb (mean 0.27 g/dl) (28). ACE inhibitors were used in the majority of patients in both groups; however, it is unlikely that their use can therefore account for the anemia in the diabetic patients, and 4 of the 13 anemic DN patients were not using ACE inhibitors.…”
Section: Figure 1-relationship Between the Natural Logarithm Of Serummentioning
confidence: 99%
“…In some patients, ACE inhibitors may cause a small decrease in serum EPO levels with a nonsignificant reduction in Hb (mean 0.27 g/dl) (28). ACE inhibitors were used in the majority of patients in both groups; however, it is unlikely that their use can therefore account for the anemia in the diabetic patients, and 4 of the 13 anemic DN patients were not using ACE inhibitors.…”
Section: Figure 1-relationship Between the Natural Logarithm Of Serummentioning
confidence: 99%
“…Clinical studies of healthy human volunteers demonstrated that Ang II administration increased serum EPO concentration by ∼35% or higher via the activation of the angiotensin II type 1 receptor (AT 1 R) (Freudenthaler et al, 1999(Freudenthaler et al, , 2000Gossmann et al, 2001). Furthermore, the Ang II-converting enzyme inhibitors captopril and enalapril that block the maturation of Ang II from Ang I, significantly decreased plasma EPO levels, by as much as ∼20-30% in another study of healthy human volunteers (Pratt et al, 1992). These findings suggest that Ang II regulates EPO production in vivo via receptordependent signaling, but the mechanism of this regulation has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of ANG II dose dependently increases Epo production (56, 57) and angiotensin-converting enzyme inhibitors (ACEi) decrease plasma Epo concentrations, likely by inhibiting ANG II formation (131). Several studies have suggested that the SNS can stimulate erythropoiesis, because reduced SNS activity is accompanied by anemia, which could be corrected by administration of Epo (18,135).…”
Section: Regulation Of Epo Productionmentioning
confidence: 99%